Efeito do Treinamento Aeróbio na Qualidade de Vida de Pacientes em Terapia Renal Substitutiva - Oliveira, Adriana Nunes de (2020)
Chronic kidney disease is defined as a slow and irreversible loss of kidney function. Patients undergoing dialysis undergo various muscle and functional changes, which favor a functional deficiency and physical inactivity, making physical activities limited. Physiotherapy rehabilitation has been inserted in hemodialysis centers, in order to provide improvement in some hemodynamic parameters, implying an improvement in quality of life (QOL). Thus, this study proposes to evaluate the effect of aerobic training during hemodialysis (HD) in patients with chronic kidney disease (CKD), by analyzing the pain index, laboratory measurements and quality of life before and after exercise. . This is a cross-sectional, prospective, quantitative study, which evaluated 16 patients with CKD undergoing HD treatment, aged between 18 and 65 years. Anthropometric, hemodynamic and laboratory data were collected when applying an aerobic training program with a portable mechanical cycle ergometer, during two HD sessions that the patients underwent for a total period of 24 weeks. The Borg effort perception scale was used to report the effort during exercise and, the Pain Mc Gill questionnaire (BR-MPQ), for pain assessment. For the analysis of QOL, the SF-36 instrument was used before and after exercise. The statistical analysis of the data was performed using means and standard deviations. The data distribution was confirmed by the Shapiro-Wilk test and the comparison of the averages during the training period was performed with the analysis of variance of repeated measures for variables with normal distribution and by means of the Friedman non-parametric test for data that were not distributed normally. Pearson's correlation was used to assess the correlation between the domains assessed by the SF-36. The results show that there was a significant difference for the subjective perception of the effort. In relation to oxygen saturation, a significant difference was found for the initial saturation between sessions 9 to 16 (designated as block 2) and sessions 17 to 24 (block 3). There was no significant difference for any of the other hemodynamic and biochemical variables, determined over the exercise period (pre, during and post training). In the QOL domains estimated by the SF-36, before and after training, a significant difference was evidenced after training in the parameters functional capacity, physical aspects, pain, social aspects and emotional aspects. With regard to pain, most participants reported not feeling any pain during exercise. The intradialytic aerobic training program can improve the functional capacity and quality of life of chronic kidney patients. Thus, it is emphasized that health care can contribute to improving the patient's QOL, providing the necessary means to face the limitations and disabilities resulting from the chronicity of health problems. Keywords: Kidney disease. Physical exercise. Renal dialysis.